2015
DOI: 10.1063/1.4919859
|View full text |Cite
|
Sign up to set email alerts
|

Dust charging and charge fluctuations in a weakly collisional radio-frequency sheath at low pressure

Abstract: Models for the charging of dust particles in the bulk plasma and in the sheath region are discussed. A new model is proposed that describes collision-enhanced ion currents in the sheath. The collisions result in a substantial reduction of the negative charge of the dust. Experimental data for the dust charge in the sheath can be described by this model when a Bi-Maxwellian electron distribution is taken into account. Expressions for the dust charging rate for all considered models are presented and their influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The second charging method examined here is the collision enhanced ion current model proposed by Piel and Schmidt 31 . In this model, the ion current includes the effect of collisions which can cause a flowing ion to become a thermal ion.…”
Section: Collision Enhanced Charging (Cec)mentioning
confidence: 99%
See 3 more Smart Citations
“…The second charging method examined here is the collision enhanced ion current model proposed by Piel and Schmidt 31 . In this model, the ion current includes the effect of collisions which can cause a flowing ion to become a thermal ion.…”
Section: Collision Enhanced Charging (Cec)mentioning
confidence: 99%
“…However, the OML model neglects charge exchange collisions which can thermalize ions that can become trapped by a negatively charged dust grain and reduce the dust grain charge. Since the collision enhanced current depends on the ion motion, there are two models that incorporate it, one for the bulk 30 where the ion velocity is low and one for the sheath 31 where the ion velocity is significant. The work by Piel and Schmidt 31 showed the effects of the collision enhanced current on the surface potential of a single dust grain, the current work examines the effects on a dust crystal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was shown that even few collisions can lead to an increase of the ion current [4,5,6,7,8,9]. We here operate with a typical gas pressure of the order of 100 Pa, where the mean free path length for ions at the gas temperature is about 100 -200 µm.…”
Section: Introductionmentioning
confidence: 99%